Best answer:
If you were asked to find the zeros, then you would be right:
(w - 8)(w + 12) = 0
The multiplication of two expression is zero: w - 8 is equal to zero or w + 12 = 0.
w = 8 or -12
But, if (w - 8)(w + 12) is equal to a nonzero number, one cannot find the solutions just by looking at the numbers.
Best answer: If you were asked to find the zeros, then you would be right:
(w - 8)(w + 12) = 0
The multiplication of two expression is zero: w - 8 is equal to zero or w + 12 = 0.
w = 8 or -12
But, if (w - 8)(w + 12) is equal to a nonzero number, one cannot find the solutions just by looking at the numbers.
9 answers
·
17 hours ago